Enhancing Fiqh Education through a Digitally Designed Linktree Portal: Focus on Acehnese Student Engagement - M. Ardiansyah; Nina Afrida; Hatta Sabri; Mahyiddin Mahyiddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines in depth the development and feasibility of a Linktree portal-based Fiqh learning media for students of Madrasah Tsanawiyah (MTs) in Aceh, with a specific case study at MTsN 1 Langsa. The background of this research is rooted in significant pedagogical challenges in Fiqh learning, where conventional methods dominated by one-way lectures often fail to stimulate the motivation and engagement of students who are digital natives. This study uses a Research and Development (R&D) approach with a 4-D model (Define, Design, Develop, Disseminate). The main contribution of this research lies in the theoretical integration between the Technology Acceptance Model in Islamic Education (TAMISE) and Cognitive Load Theory (CLT) in designing micro-learning media. The validation results show that the developed Linktree portal has very high validity (Media Expert: 94%; Material Expert: 92%) and is categorized as very feasible. Field findings indicate that the microsite information architecture on Linktree effectively reduces extraneous cognitive load through segmentation principles, while rigorous content curation ensures compatibility with Islamic values, thereby increasing technology acceptance among madrasah teachers and students. This study offers a practical and scalable solution to address the digital divide in Islamic educational institutions by leveraging efficient and user-friendly aggregator technology.